Factor Affecting Employee Motivation to Increase Performance of Sharia Bank in Indonesia on Islamic Perspective - Afif, Muhammad; Mariyanti, Tatik; Septiani, Nanda; Dolan, Ellen (Pandawan, 2023)
There is still a lack of market share for Islamic banking in Indonesia, so the purpose of this study is to analyze the effect of leadership style, job satisfaction, and work environment on employee motivation to improve the performance of Islamic banks in Indonesia. The methodology used is quantitative with the SEM Smart PLS analysis tool. The study was conducted on 200 employees of Islamic banks in Indonesia as representatives of 14 Sharia Commercial Banks (BUS) and 20 Sharia Business Units (UUS). The results of this study are the positive influence of leadership style, job satisfaction, and work environment on employee motivation and the influence of employee motivation on the performance of Islamic banks in Indonesia. Novelty in this study is leadership style, job satisfaction, and work environment in accordance with Islamic principles will be able to increase employee motivation at work, so that the performance of Islamic banks will be better and the market share of Islamic banking will also increase.